Haemocystidium spp., a species complex infecting ancient aquatic turtles of the family Podocnemididae: First report of these parasites in Podocnemis vogli from the Orinoquia. (December 2019) - González, Leydy P.; Pacheco, M. Andreína; Escalante, Ananías A.; Jiménez Maldonado, Andrés David; Cepeda, Axl S.; Rodríguez-Fandiño, Oscar A.; Vargas‐Ramírez, Mario; Matta, Nubia E.
Abstract: The genus Haemocystidium was described in 1904 by Castellani and Willey. However, several studies considered it a synonym of the genera Plasmodium or Haemoproteus . Recently, molecular evidence has shown the existence of a monophyletic group that corresponds to the genus Haemocystidium . Here, we further explore the clade Haemocystidium spp. by studying parasites from Testudines. A total of 193 individuals belonging to six families of Testudines were analyzed. The samples were collected in five localities in Colombia: Casanare, Vichada, Arauca, Antioquia, and Córdoba. From each individual, a blood sample was taken for molecular analysis, and peripheral blood smears were made, which were fixed and subsequently stained with Giemsa. The prevalence of Haemocystidium spp. was 1.55% (n = 3/193); all infected individuals belonged to Podocnemis vogli (Savanna Side-necked turtle) from the department of Vichada. This is the first report of Haemocystidium spp. in Colombia and in this turtle species. The phylogenetic analysis of a mitochondrial c ytb fragment revealed Haemocystidium spp. as a monophyletic group and as a sister taxon of Haemoproteus catharti and the genus Plasmodium . Haemocystidium spp. are difficult to identify by morphology only. As a result, it is possible that some of the taxa, such as Haemocystidium ( Simondia ) pacayae, represent a species complex. The parasite found in our study is morphologically indistinguishable from Haemocystidium ( Simondia ) pacayae reported in Peru. However, the new lineage found in P. vogli shows a genetic distance of 0.02 with Hae. pacayae and 0.04 with Hae. peltocephali . It is proposed that this divergent lineage might be a new species. Nevertheless, additional molecular markers and ecological features could support this hypothesis in the future. Graphical abstract: Image 1 Highlights: Haemocystidium spp. now reported in Podocnemis vogli in Colombia. Haemocystidium spp. are cryptic species in Podocnemididae. Our data support that Haemocystidium is a monophyletic group that shares a recent common ancestor with the genus Plasmodium .